Концепция ассоциированного пространства и геометрическое конструирование кинематических моделей - Костинский, А.С. (Видавничий дім "Академперіодика" НАН України, 2009)
У рамках пiдходу до опису осередку землетрусу с позицiй механiки збудливих середовищ дослiджується зiставлений “квазiдинамiчнiй” моделi абстрактний асоцiйований простiр, мiнливий поза часом як послiдовнiсть геометричних образiв. Побудовано аксiоматику оптимальної еволюцiї та показано, що принцип максимальної простоти визначає метрику як розв’язок рiвнянь Ейнштейна з космологiчної постiйної. In the context of an approach to the description of an earthquake focus from the positions of excitable medium mechanics, the abstract associated space related to a “quasidynamic” model and varying out of time as a chain of geometric images is studied. The optimal evolution axiomatics is built up, and it is shown that the “maximal simplicity principle” determines the metric as a solution of the Einstein equations including the cosmological constant.